2022
DOI: 10.3390/d14050322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Population Structure of Croatian Local Donkey Breeds

Abstract: The two native Croatian donkey breeds (Littoral-Dinaric donkey and Istrian donkey) were marginalized in the second half of the 20th century and were on the verge of biological extinction. The aim of this study was to analyze the demographic and genetic status of two donkey breeds, two decades after the start of protection by analyzing their pedigrees and genetic structure. The average generation interval was higher for the Istrian donkey (7.73) than for the Littoral-Dinaric donkey (7.27). The rate of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Currently, the Istrian donkey population with offspring is approximately 860 animals, while the Littoral Dinaric donkey population is around 3680 animals [ 6 ]. The Istrian donkey and the Littoral Dinaric donkey have been described in terms of conformation [ 7 ] and genetic structure [ 8 ]. However, ensuring the long-term sustainability of these local donkey breeds requires their economic repositioning, the creation and optimization of economic utilization programs, and improved collaboration among all stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Istrian donkey population with offspring is approximately 860 animals, while the Littoral Dinaric donkey population is around 3680 animals [ 6 ]. The Istrian donkey and the Littoral Dinaric donkey have been described in terms of conformation [ 7 ] and genetic structure [ 8 ]. However, ensuring the long-term sustainability of these local donkey breeds requires their economic repositioning, the creation and optimization of economic utilization programs, and improved collaboration among all stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies demonstrated the advantages of employing mtDNA for population genetics research in donkeys [13,21,40]. The origin of domestic donkeys can be traced back to African wild asses through an analysis of mitochondrial and nuclear DNA [41]. Mitochondrial DNA studies have identified two distinct lineages in domestic donkeys: clade I, also known as the Nubian lineage, which includes domestic donkeys and the Nubian wild ass (Equus africanus africanus); and clade II, believed to have originated from an extinct African wild ass population, possibly similar to the Somali wild ass (Equus africanus somaliensis) [2,4].…”
Section: Mitochondrial Dna As a Tool For Assessing Donkey Biodiversitymentioning
confidence: 99%
“…Croatian donkeys (Istrian, North Adriatic, and Littoral-Dinaric) [41] MGAT4C, NTS, POLR3B, TCP11L2, and TMEM263, KITLG…”
mentioning
confidence: 99%